Women’s Suffrage Through the CLIL Approach - Sabrina Buchara; Fernanda Catalán Soto; Estefanía Gutierrez; Daiana Paola Galindez Peña (Latin American Journal of Content and Language Integrated Learning, 2023)
The aim of this article is to improve and develop students’ critical thinking as well as their linguistics skills by making use of the CLIL approach. Focusing on relevant topics in today's society such as the voting system is an interesting opportunity not only to motivate students' learning, but also to be aware of the world they live in. The activities are designed for students around the voting age in Argentina with an intermediate level of English. Through the development of writing and speaking skills and collaborative work, students will be aware of the importance of past events such as the women’s suffrage, and social differences that are still happening all over the world.